Progress of a gas-electron-multiplier based camera (GEM) in investigating EAST macroscopic instabilities. (1st May 2023) - Li, Erzhong; Chen, Y; Qu, H; Zhou, T; Chen, F; Zhang, L; Wang, H; Duan, Y; Liu, H; Shen, B; ,
Abstract: In recent years magneto-hydrodynamic instabilities have been observed in different experimental scenarios by a gas electron multiplier (GEM) camera, since it was installed on the Experimental Advanced Superconducting Tokamak (EAST). The GEM camera is set up outside the EAST vacuum chamber to record x-ray photons through a beryllium window, which has obtained valuable data for analysis: (1) neoclassical tearing mode (NTM) onset and (2) plasma disruption dynamics in the presence of magnetic islands. Although not precisely compared with theory and simulations, the GEM, in synergy with other diagnostics, reveals the significance of electron dynamics in NTM and plasma disruption. This is meaningful for understanding and modeling the disruption instability of fusion plasmas.